1999
DOI: 10.1364/ol.24.001549
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-doped SiO_2 glasses for F_2 excimer laser optics:?fluorine content and color-center formation

Abstract: Color-center formation in F-doped, OH-free synthetic SiO(2) glasses by irradiation with F(2) excimer lasers (157 nm) was examined as a function of the F content. The concentration of photoinduced E(') centers was reduced to approximately 1/20 by 1 mol.% F(2) doping and remained almost constant on further doping to 7.3 mol. %. The absorption edge was considerably shifted to a lower wavelength (157.4 nm -->153 nm for a 5-mm-thick sample) by 1-mol. % doping and decreased only slightly on further doping. The inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 12 publications
1
26
0
1
Order By: Relevance
“…The addition of 1 mol% (approximately 0.33 wt%) fluorine to pure silica results in a relatively large blueshift of the absorption edge [12]. Further additions of fluorine, ranging from 1.5 to 7.3 mol%, do little to improve the UV transmission of these glasses, especially at 157 nm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of 1 mol% (approximately 0.33 wt%) fluorine to pure silica results in a relatively large blueshift of the absorption edge [12]. Further additions of fluorine, ranging from 1.5 to 7.3 mol%, do little to improve the UV transmission of these glasses, especially at 157 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Further additions of fluorine, ranging from 1.5 to 7.3 mol%, do little to improve the UV transmission of these glasses, especially at 157 nm. Moreover, the resistance of these glasses against formation of color centers on laser exposure also increases on initial addition of fluorine to up to 1 mol% and the effect saturates at higher fluorine concentrations [12]. It was hypothesized in these studies that the role of initial addition of fluorine is to widen the optical band-gap by removal of the strained bonds in the structure of amorphous silica that may have high-energy electronic states associated with them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). As for optical materials, Hosono et al 5 reported novel photosensitive or photorefractive glasses, SiO 2 glasses, 6 and CaF 2 crystal 7 for excimer laser applications. These materials were found through accumulated fundamental research on defects in glass and dielectric crystals.…”
Section: Researchmentioning
confidence: 99%
“…7 In low-GeO 2 (i.e., 5%) glasses, the 157-nm photons directly bridge the ϳ7.1-eV bandgap, 8 which allows access to strong single-photon photosensitivity mechanisms without the need for traditional enhancement techniques. 3 -5 In this Letter we describe, for what is to our knowledge the first time, the formation of strong and good-quality LPFGs in standard single-mode f ibers (Corning SMF-28) without fiber pretreatment.…”
mentioning
confidence: 99%